La bailo terapia infantil en el desarrollo de la inteligencia emocional de los niños y niñas de segundo año de educación básica de la unidad Educativa Fiscomisional “San Vicente de Paúl”, cantón riobamba, provincia de Chimborazo. período 2016. - Solís Galarza, Myriam Mercedes (2017)
The research entitled "The child's dance therapy in the development of emotional intelligence of children", arises in order to stimulate memory, coupling, sense of hearing, encouraging the development of rhythm, toning muscles, decreasing the Overweight, developing their emotional intelligence; Allowing the body to release toxins and improve the quality of life, promoting cognitive development in the second year of basic education of the San Vicente de Paúl "San Vicente de Paúl" educational unit in Riobamba, province of Chimborazo. Period 2016. Being its main objective "To establish to the dance children's therapy in the development of the emotional intelligence of the second year children of Basic Education of the Educative Educational Unit San Vicente de Paúl, Canton Riobamba, Province of Chimborazo, Period 2016 ". Methodologically it was a quasi-experimental investigation, of bibliographical type and of field. The participating population was constituted by 124 students of the second year of Basic Education. General methods such as the hypothetico-deductive, the inductive-deductive, and the analytic-synthetic were used; The same that started from the observation, a theoretical support, the establishment and verification of the hypothesis, establishing the respective conclusions and recommendations. We used the technique of observation and the instrument was the observation sheet made up of measurement parameters that will allow us to study and find the relationship between both study variables. In addition, when implementing the Bailo-therapy Guide to develop emotional intelligence, it is concluded that both teachers and parents were not aware of the most appropriate way to develop emotional intelligence in children, so they could not adapt to the environment Educational emergence different problems in their learning and daily coexistence with their peers unable to express themselves comfortably. Thus, in applying the Dance-Therapy Guide, most of the children were able to adapt better to their environment, which allowed them to express themselves more easily and socialize with their classmates; So its use is recommended as an excellent means to motivate the child in the development of their different capacities whether emotional, physical, motor, etc.